Three-point intrinsic alignments of dark matter haloes in the IllustrisTNG simulation. Issue 2 (22nd August 2022) - Pyne, Susan; Tenneti, Ananth; Joachimi, Benjamin
ABSTRACT: We use the IllustrisTNG suite of cosmological simulations to measure intrinsic alignment (IA) bispectra of dark matter subhaloes between redshifts 0 and 1. We decompose the intrinsic shear field into E- and B- modes and find that the bispectra B δδE and B δEE, between the matter overdensity field, δ, and the E-mode field, are detected with high significance. We also model the IA bispectra analytically using a method consistent with the two-point non-linear alignment model. We use this model and the simulation measurements to infer the IA amplitude A IA and find that values of A IA obtained from IA power spectra and bispectra agree well at scales up to k_max= 2 h Mpc^-1 . For example at z = 1, A IA = 2.13 ± 0.02 from the cross power spectrum between the matter overdensity and E-mode fields and A IA = 2.11 ± 0.03 from B δδE . This demonstrates that a single physically motivated model can jointly model two-point and three-point statistics of IAs, thus enabling a cleaner separation between IAs and cosmological weak lensing signals.